1987
DOI: 10.1002/1098-108x(198705)6:3<409::aid-eat2260060311>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Self-help dieting strategies in college males and females

Abstract: The present study sought to determine the self‐help dieting strategies used by college men and women. There were 204 adults (102 males, 102 females) asked (1) the degree of importance placed on achieving and maintaining their ideal weight, (2) the reasons (i. e., health, appearance, or psychological) for dieting, and (3) the specific types of food restriction and physical activity methods used. Results indicated that females were much more likely to have actively dieted during the past 6 months and were more l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 15 publications
3
28
0
Order By: Relevance
“…[17][18][19] Studies also have found that girls are more likely than boys to report weight concerns, 6,20 so weight concerns may play a greater role in smoking initiation and maintenance for girls than for boys. Smokers, especially females, often report that they use cigarettes as a weight-control strategy, 17,[21][22][23] and dieters are more likely than nondieters to report retrospectively that they initiated smoking to lose weight or to prevent weight gain. 24 Another possible mechanism linking dieting and smoking suggests that dieting may itself be a psychologic or physiologic potentiating factor that heightens the risk for smoking.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Studies also have found that girls are more likely than boys to report weight concerns, 6,20 so weight concerns may play a greater role in smoking initiation and maintenance for girls than for boys. Smokers, especially females, often report that they use cigarettes as a weight-control strategy, 17,[21][22][23] and dieters are more likely than nondieters to report retrospectively that they initiated smoking to lose weight or to prevent weight gain. 24 Another possible mechanism linking dieting and smoking suggests that dieting may itself be a psychologic or physiologic potentiating factor that heightens the risk for smoking.…”
Section: Discussionmentioning
confidence: 99%
“…We also hypothesized that the accentuated body dissatisfaction of gay men would influence their reasons for exercise. Recent research has found that college women more than men reported that their exercise was motivated by weight-related reasons (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Klesges et al (18) reported that college females are more likely than male counterparts to engage in healthy and unhealthy physical activity and food restriction behaviors and place higher importance on appearance benefits of maintaining an ideal body weight.…”
Section: Discussionmentioning
confidence: 99%